The pedagogical genius of education and the vicissitudes of today's education - Roberto Herrera Correa (Corporación Universitaria Minuto de Dios, 2005)
This article covers the life and work of Comenius. In this recount, the article primarily defines what didactic is. It follows on to describe the three types of didactic is. It follows on to describe the three types of didactic. These are the Mathetic or student focussed approach, the Systematic or teacher-train-ing approach, and the Methodic that is school based. Finally, the author presents a synthesis of the three and the way they are presented in the Colombian context.